Determination of trade-off-functions to analyse the provision of agricultural non-commodities. (8th March 2006) - Sattler, Claudia; Schuler, Johannes; Zander, Peter
Multi-functionality of agriculture has become a crucial issue in WTO negotiations on agriculture trade. The theoretical classification of agricultural products into Commodity (CO) and Non-Commodity Outputs (NCO) by the OECD provided a framework for further analysis. The operationalisation of the concept of multi-functionality of agriculture requires detailed analyses of the nature of jointness between NCO and CO production, the level of NCO related to different types of production technology and the related production costs. Using the bio-economic modelling system MODAM, both an economic and ecological assessment of CO and NCO production can be performed. A fuzzy-logic tool processing expert knowledge assesses the environmental effects of agricultural production activities, while an economic evaluation provides information on their profitability. A farm level optimisation module allows for simulation of the production activities both at field, farm and regional level. Trade-off functions demonstrate the interdependencies of the analysed outputs.